Continuous synthesis of palladium nanorods in oxidative segmented flow. Issue 2 (23rd September 2015) - Sebastian, Victor; Basak, Soubir; Jensen, Klavs F.
Abstract : Laminar and segmented flow methods are presented for producing Pd rod‐shaped nanostructures from Na2 PdCl4 in mixtures of water, ethylene glycol, polyvinyl pyrrolidone, and KBr. Synthesis in laminar flow produced an evolution from Pd nanoparticles to short nanorods with residence time. Use of air as the segmentation gas tuned the oxidative environment promoting anisotropic growth of Pd. Moreover, the elevated temperatures (160°C and 190°C) and pressure (0.8 MPa) reduced the synthesis time from hours for most batch systems to 2 min. The ratio of polyol and Pd precursor metal flow streams controlled the anisotropic growth, obtaining nanorods with a diameter approximately 4 nm and an aspect ratio up to 6. Nanorods were single crystal with the 100 lattice spacing of fcc structure, and without any dislocation, stacking fault, or twin defects. The resulting Pd nanorods had high activity at moderate temperature (40ºC) and pressure (0.2 MPa) in the catalytic hydrogenation of styrene. © 2015 American Institute of Chemical Engineers AIChE J, 62: 373–380, 2016